Dynamic gene order on the Silene latifolia y chromosome - Howell, E; Armstrong, S; Filatov, D (2011)
Dioecious Silene latifolia evolved heteromorphic sex chromosomes within the last ten million years, making it a species of choice for studies of the early stages of sex chromosome evolution in plants. About a dozen genes have been isolated from its sex chromosomes and basic genetic and deletion maps exist for the X and Y chromosomes. However, discrepancies between Y chromosome maps led to the proposal that individual Y chromosomes may differ in gene order. Here, we use an alternative approach, with fluorescence in situ hybridization (FISH), to locate individual genes on S. latifolia sex chromosomes. We demonstrate that gene order on the Y chromosome differs between plants from two populations. We suggest that dynamic gene order may be a general property of Y chromosomes in species with XY systems, in view of recent work demonstrating that the gene order on the Y chromosomes of humans and chimpanzees are dramatically different. © 2011 Springer-Verlag.